A brief Review on the Nano-biosensors in the Agriculture Area (International Journal of Innovative Research in Computer Science & Technology, 2022)
Nanotechnology emerged as gift to  mankind, with great potential in a broad variety of areas of  research and our everyday life. In contrast to conventional  biosensors, the application of nanotechnology in the creation  of biosensors results in a highly effective nano-biosensor  with a tiny shape. Nano- and Nano sensors based keen delivery systems can be used to monitor the release of  agrochemicals for pest and pathogen defense, to detect the  presence of plant viruses, to determine soil nutrient content,  and to release nano-encapsulated slow-release fertilizers  without wasting them by leaching. As a consequence, there  is a lot of optimism that such robots may assist maintain  agriculture by boosting output and productivity.  Nanotechnology has emerged as a gift to mankind, with great  potential in a broad variety of areas of research and in our  everyday lives. As nanotechnology is utilized to improve  biosensors, it results in a more resilient nano-biosensor with  a smaller structure than conventional biosensors. Nano biosensors may detect wide variety of fertilizers, herbicides,  pesticides, insecticides, bacteria, moisture, and soil pH,  among other things. When utilized correctly and in a  controlled way, nano-biosensors may assist to promote  sustainable agriculture and impro
Keywords: Agriculture; Biosensors; Herbicides; Nano-biosensors; Nanotechnology